Formulasi Korporasi sebagai Subjek Hukum Pidana dalam Regulasi Lingkungan Hidup di Indonesia - Mujiono, Mujiono; Tanuwijaya, Fanny (University of Jember, 2019)
The existence of human life is extremely dependent on the environment, and the environment has provided free various needs for humans, which is an absolute requirement so that humans can maintain their lives. Environmental problems are essentially human ecological problems and environmental problems arise as a result of environmental pollution. This is an element of many negligence errors committed by companies or legal entities that operate, including the element of deliberate and negligent use of environmental law through Law No. 32 of 2009, concerning Environmental Protection stated in Article 116 UUPPLH. Corporate liability in environmental crime is the subject of discussion in cases with the decision register number No.1405K / Pid.Sus / 2013, namely PT. KARAWANG PRIMA SEJAHTERA (PT. KPSS), which is engaged in the metal, steel, and export-import aluminum and trade industry. In its location, PT KPSS produces Aero Slag waste from iron and steel smelting, bottom ash waste and fly ash obtained from the burning of coal in power plans. The criminal responsibility of environmental crimes is also carried out by PT KALISTA ALAM, which operates in the fields of plantation, industry, supplier, and shipping in the oil palm business. In its violation, PT KALISTA ALAM has opened land by burning it, which is carried out continuously to expand oil palm cultivation/ In the verdict, No. 131 / Pid.B / 2013 / PN.MBO, the company was charged for committing environmental crimes. Keyword: Environmental Pollution, Environmental Crime, Criminal Accountability